Survival in Ecuadorian Patients with Prostate Cancer Clinically Treated with Radiotherapy and Chemotherapy - Alberto Sánchez Garrido; Guido Nino Guida Acevedo; Becker Neto Mullo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2024)
Foundation: prostate cancer is a common oncological condition in men. The study of treatments, effectiveness and survival is a necessity. Objective: to compare survival in ecuadorian patients with prostate cancer treated clinically with radiotherapy and chemotherapy in a hospital in the Amazon region. Method: an observational, analytical prospective cohort study was carried out in 74 patients with prostate cancer. The variables were analyzed: survival time, treatment, survival function, risk function. It was developed in two phases, in the first the average survival time of the patients was calculated, while in the second the comparison of survival between patients treated with radiotherapy and chemotherapy was carried out. The Chi-square test and the Log Rank (Mantel-Cox) statistic were used to evaluate significant differences in survival distributions between the groups. Results: the mean overall survival was 46.2 months; higher in the group that received radiotherapy (50.3 months) compared to the chemotherapy group (39.4 months). Greater cumulative survival was observed in patients who received radiotherapy. In the chemotherapy group, the cumulative risk curve tended to increase more steeply as the months passed compared to the radiotherapy group; however, no statistically significant difference in survival was identified between groups (p > 0 .05) Conclusions: greater survival was found in the group that received radiotherapy, however, no significant difference in survival was found between groups.